HGG-14. PEDIATRIC BITHALAMIC DIFFUSE GLIOMAS ARE DISTINGUISHED FROM THEIR UNILATERAL COUNTERPARTS BY FREQUENT EGFR EXON 20 INSERTIONS AND RARE HISTONE H3 MUTATIONS. (23rd April 2019) - Lee, Julieann; Ferris, Sean; Sloan, Emily; Hofmann, Jeff; Samuel, David; Scharnhorst, David; Siongco, Aleli; Li, Rong; Jin, Lee-way; Antony, Reuben; Alashari, Mouied; Cheshier, Samuel; et al.
Abstract: Though diffuse gliomas arising in the thalamus of children frequently harbor K27M mutation in the histone H3 genes H3F3A or HIST1H3B, children with diffuse gliomas involving the bilateral thalami at presentation often lack histone H3 mutations (Broniscer et al, Brain Pathology 2018). In order to investigate the molecular pathogenesis of pediatric bithalamic diffuse gliomas, we performed comprehensive genetic profiling of seven cases (ages 3–11 years). Six tumors (86%) harbored mutations in the EGFR oncogene in the absence of accompanying EGFR amplification. Four of these EGFR mutations were small in-frame insertions/duplications within exon 20 that encodes a portion of the intracellular tyrosine kinase domain, where mutations are common in lung adenocarcinoma and fibrous hamartoma of infancy but are not typically present in gliomas. The other two cases with EGFR mutations were located in the extracellular ligand-binding domain, where mutations and rearrangements are common in IDH-wildtype glioblastomas in the cerebral hemispheres of adults. Additional pathogenic alterations included TP53 mutation (n=4 cases), CDKN2A homozygous deletion (1), CDK6 amplification (1), CDKN2C mutation (1), TERT promoter mutation (1), HIST1H3B K27M mutation (1), and truncating mutations involving the BCOR (1), BCORL1 (2), LZTR1 (1), and CREBBP (1) transcriptional regulatory genes. No tumors harbored pathogenic alterations involving the H3F3A, HIST1H3C, SETD2, PDGFRA, MET, PPM1D, ACVR1, FGFR1, BRAF, PTPN11, IDH1, IDH2, MYB, and MYBL1 genes. In comparison, EGFR mutations are rare (<1% of 982 cases) in pediatric high-grade gliomas in general (Mackay et al, Cancer Cell 2017). Together, these findings identify pediatric bithalamic diffuse gliomas as a unique subtype of IDH-wildtype and mostly histone H3-wildtype high-grade glioma characterized by frequent EGFR kinase domain mutations, with implications for precision medicine treatment using small molecule kinase inhibitors such as poziotinib, a CNS-penetrant agent with selective activity against exon 20 mutant EGFR.